Palaeobiogeographical implications of the earliest botryopterid ferns in Cathaysia. (2nd November 2021) - Zhou, Wei-Ming; Pšenička, Josef; Hilton, Jason; Wang, Jun
ABSTRACT: The Wuda Tuff Flora from the Taiyuan Formation of Inner Mongolia is a palaeobotanical lagerstätte that is key to our current understanding of the composition and ecology of the earliest Permian Cathaysian floras. We investigate an anatomically preserved axis that represents an additional plant family recorded in this flora and considers its palaeobiogeographical implications. The specimen possesses an ω-shaped vascular strand and has features that conform to the botryopterid fern Botryopteris . Comparisons indicate greatest similarity with Botryopteris scottii from the Pennsylvanian of England but due to limited information we assign it to Botryopteris cf. scottii . The new finding represents the earliest stratigraphic occurrence of botryopterids in the Cathaysian floras. Alongside Botryopteris tridentata and Botryopteris cf. forensis in slightly younger Cisuralian strata from China, it demonstrates migration of closely related species from the Pennsylvanian wetlands of Euramerica into the Permian wetlands of Cathaysia. Together with unexpectedly early stratigraphic occurrences of the 'Methuselah taxa' Yuania, Gigantonoclea and Autunia in the roof shale flora of the coal seam overlying the Wuda Tuff Flora, B . cf. scottii adds to a growing body of evidence that records significant floral interchange and migration from different ecological settings in the Cathaysian and Euramerican floras by the earliest Permian.